STUDI KASUS LAYANAN KONSELING INDIVIDU DENGAN PENDEKATAN CBT DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL SISWA MONODACTYLY DI SEKOLAH INKLUSI - Moh. Rifki; Dewi Masyitoh; Ade Irma Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning motivation is not the only obstacle inclusive schools must address; students with physical differences such as monodactyly, a congenital limb malformation marked by fewer than normal fingers, often face low self-confidence, social withdrawal, and peer mockery that hinder the development of their social skills. This study aims to describe the implementation of individual counseling services using the Cognitive Behavioral Therapy (CBT) approach, identify supporting and inhibiting factors, and analyze its effectiveness in developing the social skills of a monodactyly student at MTs Hidayatul Munawwarah Silo, Jember. A qualitative case study approach was used, with five informants selected through purposive sampling: the monodactyly student, the guidance and counseling teacher, the homeroom teacher, the head of madrasah, and a parent. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles, Huberman, and Saldaña model. The results show that CBT-based individual counseling was implemented through three stages, assessment, intervention, and evaluation. Supporting factors included institutional policy support and collaboration between the counseling teacher and the homeroom teacher, while inhibiting factors included the student's persistent shyness, peer stigma, and limited disability-friendly facilities. The service proved effective in developing four aspects of the student's social skills, cognitive, behavioral, emotional, and social independence, although the changes remained gradual and required continued support.